(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Summary of forecasting method of heat insulated and moisture tight concrete products which maturing develops without heat carrying agent use is presented. Two stages of research carrying out are proposed. Experimentaldata of the first research stage are shown. Keywords: concrete sample, cement heat evolution, experiment.